Arithmetic program paths. - Renieris, Manos
We present Arithmetic Program Paths, a novel, efficient way to compress program control-flow traces that reduces program bit traces to less than a fifth of their original size while being fast and memory efficient. In addition, our method supports online, selective tracing and compression of individual conditionals, trading off memory usage and compression rate. We achieve these properties by recording only the directions taken by conditional statements during program execution, and using arithmetic coding for compression. We provide the arithmetic coder with a probability distribution for each conditional that we obtain using branch prediction techniques. We implemented the technique and experimented on several SPEC 2000 programs. Our method matches the compression rate of state-of-the-art tools while being an order of magnitude faster.
Keywords: Software; Software engineering; Testing and debugging; Tracing; Data; Coding and information theory; Data compaction and compression; Experimentation; Measurement; Performance; Arithmetic coding; Bit-tracing.; Branch prediction